THE RELATIONSHIP BETWEEN ENTREPRENEURSHIP VALUES OF PRIMARY SCHOOL TEACHERS AND THEIR PERCEIVED SOCIAL SUPPORT LEVELS - Türkan ARGON (Fırat University, 2019)
The study aimed to identify the relationship between entrepreneurship values of primary school teachers and their perceived social support levels and to determine whether there was a significant relationship between their views regarding perceived social support and entrepreneurship values. The descriptive study employed a relational screening model and simple random sampling. 287 teachers working in 39 public primary schools during the 2011-2012 educational year were contacted. “Scale of Entrepreneurship Values” and “Multi Scale of Dimensional Perceived Social Support” were used as data collection tools. Frequencies, percentages, arithmetic means, standard deviation, t-test, Kruskal Wallis, Pearson Product-Moment Correlation Coefficient were used in data analysis. Some of the findings of the study are as follows: According to entrepreneurship values of teachers, the highest mean was found to be “freedom” sub dimension and the lowest mean was “obedience” sub dimension. According to perceived social support levels, social support perceived in family, friends and significant other levels were found to be high. Personal characteristics of teachers were not found significant in any sub dimension in terms of perceived social support. In terms of entrepreneurship values; variable “age” was found to be significant in “freedom” sub dimension whereas variable “gender” and “content with profession” sub dimensions were found to be meaningful in “passive” sub dimension. The relationship between entrepreneurship values of teachers and their perceived social support was found to be low.